PENERAPAN METODE PENYUSUTAN MENURUT KETENTUAN PAJAK DAN PENGARUHNYA TERHADAP PAJAK PENGHASILAN BADAN DI PT BUANA RANTAI BERKAT ABADI MEDAN - Stefvy; Denny Salim (Jurnal Studi Akuntansi Pajak Keuangan, 2024)
This research was conducted at PT Buana Chain Berkat Abadi Medan. This company is a spare parts distributor. The company has many fixed assets. Depreciation costs have an impact on company profits. Companies realize that the right depreciation method can minimize corporate tax income in a particular tax year. However, the depreciation method must be carried out based on the Income Tax Provisions in calculating tax income correctly. Company employees do not have sufficient experience and skills in taxation. Under these conditions, there is a possibility that employees may make mistakes in applying the depreciation method based on the Income Tax Provisions. The correct depreciation method in accordance with the Income Tax Provisions has an impact in determining the correct Corporate Income Tax. This research will analyze the application of depreciation methods in companies so that companies can recognize depreciation costs correctly in calculating the entity's tax income. In addition, this research can provide information on appropriate depreciation methods that can be used to minimize income tax payments for a particular tax year.